PENGARUH UMUR PERUSAHAAN, UKURAN PERUSAHAAN, LIKUIDITAS DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN PADA MASA COVID-19 - Siti Yusina Utami Putri; Ickhsanto Wahyudi (GoAcademica Research dan Publishing, 2022)
The purpose of carrying out this research is to be able to identify and test various factors that can influence factors in influencing accuracy when providing financial reports for public companies in Indonesia during the pandemic period. The method used in this research is through logistic regression analysis. This analysis will be assisted by using statistical application tools. The results of this study found that there is a simultaneous influence that comes from profitability, liquidity, company age and also the size of the company to the timeliness in submitting financial statements belonging to property companies that have been registered by property companies on the Indonesia Stock Exchange. There is a positive influence given by the age of the company to the delivery of the company's financial statements. In contrast to the size of the company, where this has a negative influence on the accuracy in submitting the company's financial statements. The liquidity and profitability have no influence at all on the submission of financial statements in a company.